Critical Discourse Analysis of Ambonese Pop Songs - Prasojo Yekti Perdana (Yayasan Baru Haji Samsudin, 2025)
This qualitative study analyzes the content of five Ambonese pop songs to explore themes of criticism, freedom of life, love betrayal, and self-determination, and to understand the use of translingualism in music. The research employs directed content analysis, drawing on existing theories and hypotheses to guide the analysis. The samples in the study are five Ambonese pop songs: